Pesticides Toxic Aspects - Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2014)
The edited book Pesticides - Toxic Aspects contains an overview of attractive researchers of pesticide toxicology that covers the hazardous effects of common chemical pesticide agents employed every day in our agricultural practices. The combination of experimental and theoretical pesticide investigations of current interest will make this book of significance to researchers, scientists, engineers, and graduate students who make use of those different investigations to understand the toxic aspects of pesticides. We hope that this book will continue to meet the expectations and needs of all interested in different aspects of pesticide toxicity.